Widespread circulation of West Nile virus, but not Zika virus in southern Iran. - Mazyar Ziyaeyan; Mohammad Amin Behzadi; Victor Hugo Leyva-Grado; Kourosh Azizi; Gholamreza Pouladfar; Hedayat Dorzaban; Atoosa Ziyaeyan; Sanaz Salek; Aghyl Jaber Hashemi; Marzieh Jamalidoust (Public Library of Science (PLoS), 2018)
West Nile virus (WNV) and Zika virus (ZIKV) are mosquito-borne viral infections. Over the past few decades, WNV has been associated with several outbreaks involving high numbers of neuroinvasive diseases among humans. The recent re-emergence of ZIKV has been associated with congenital malformation and also with Guillain-Barre syndrome in adults. The geographic range of arthropod-borne viruses has been rapidly increasing in recent years. The objectives of this study were to determine the presence of IgG specific antibodies and the genome of WNV and ZIKV in human samples, as well as WNV and ZIKV genomes in wild-caught mosquitoes in urban and rural areas of the Hormozgan province, in southern Iran. A total of 494 serum samples were tested for the presence of WNV and ZIKV IgG antibodies using ELISA assays. One hundred and two (20.6%) samples were reactive for WNV IgG antibodies. All serum samples were negative for ZIKV IgG antibodies. Using the multivariable logistic analysis, age (45+ vs. 1-25; OR = 3.4, 95% C.I.: 1.8-6.3), occupation (mostly outdoor vs. mostly indoor; OR = 2.4, 95% C.I.: 1.1-5.2), and skin type(type I/II vs. type III/IV and type V/VI; OR = 4.3, 95% C.I.: 1.7-10.8 and OR = 2.7, 95% C.I.: 1.3-5.5 respectively, skin types based on Fitzpatrick scale) showed significant association with WNV seroreactivity. We collected 2,015 mosquitoes in 136 pools belonging to 5 genera and 14 species. Three pools of Culex pipiens complex were positive for WNV RNA using real-time reverse transcription polymerase chain reaction (rtRT-PCR). ZIKV RNA was not detected in any of the pools. All WNV ELISA reactive serum samples were negative for WNV RNA. In conclusion, we provided evidence of the establishment of WNV in southern Iran and no proof of ZIKV in serum samples or in mosquito vectors. The establishment of an organized arbovirus surveillance system and active case finding strategies seems to be necessary.